2009
DOI: 10.1111/j.1467-6427.2009.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing family inclusive acute inpatient mental health services: a staff training programme in Somerset

Abstract: In spite of policies advocating the involvement of families in the care of mental health service users in the UK there are few examples of training initiatives to bring this about. This article describes the delivery of a whole‐team training initiative to promote family inclusive working in all acute inpatient units in Somerset. The three‐day staff‐training programme is described and training outcomes are reported. Staff reported a significant increase in confidence in their skills for working with families, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
0
27
0
1
Order By: Relevance
“…Involving family members in treatment and care is advocated as an important aspect of service user involvement. There are studies reporting that family members would like more information, more time and support from the mental health services, as well as greater involvement in the planning of their relatives' care and services (Goodwin & Happell, 2006;Stanbridge, Burbach, & Leftwich, 2009). Providers' reports of carer involvement increased in the intervention group and decreased in the comparison group.…”
Section: Loadingsmentioning
confidence: 98%
“…Involving family members in treatment and care is advocated as an important aspect of service user involvement. There are studies reporting that family members would like more information, more time and support from the mental health services, as well as greater involvement in the planning of their relatives' care and services (Goodwin & Happell, 2006;Stanbridge, Burbach, & Leftwich, 2009). Providers' reports of carer involvement increased in the intervention group and decreased in the comparison group.…”
Section: Loadingsmentioning
confidence: 98%
“…Attendees at a 6-month follow-up session reported more contact with families. Stanbridge, Burbach, & Leftwich (2009) undertook team training on an acutecare inpatient unit and found that a record audit showed increased consideration of the needs of families posttraining and that staff reported increased confidence in working with families after the training.…”
Section: Development Of Family Involvement Standards 85mentioning
confidence: 98%
“…Furthermore, results from multiprofessional efficacy studies on psychoeducational interventions and cognitive behavioral interventions for these distressed families, especially for families of schizophrenic, bipolar, and substance‐use disorder patients, have shown improvements in family functioning and better psychosocial outcomes for the patients when family interventions are being used . In spite of scientific evidence and clinical experience that family interventions have shown positive effects for the well‐being and functioning of patients and families, these programs, methods, and interventions have been a great challenge with systems barriers to implement into multidisciplinary everyday adult psychiatry …”
Section: Introductionmentioning
confidence: 99%